Epstein-Barr Virus-Based Nasopharyngeal Carcinoma (NPC) Risk Prediction Scores Are Elevated in NPC Multiplex Family Members in Taiwan - Lee, Mei-Hsuan; Huang, Yu-Han; Coghill, Anna E; Liu, Zhiwei; Yu, Kelly J; Hsu, Wan-Lun; Chien, Yin-Chu; Wang, Cheng-Ping; Chen, Tseng-Cheng; Chen, Chien-Jen; Hildesheim, Allan (The Journal of infectious diseases, 2021)
Abstract Nasopharyngeal carcinoma (NPC) is caused by Epstein-Barr virus (EBV) and is more likely to occur in susceptible families. Whether genetic susceptibility operates through altered EBV control is incompletely understood. We used a NPC risk prediction model based on 14 EBV markers to compare risk score distribution in unaffected members from multiplex families with that in population-based controls. Despite the absence of NPC at the time of antibody measurement, we observed an upward shift in risk score among multiplex family members compared to the general population, consistent with the possibility that genetic factors affect NPC risk through alterations in EBV control.